The role of bioactive polyphenols from anacardium occidentale linn. leaves on α-amylase and dipeptidyl peptidase iv activities for type 2 diabetes mellitus management - Haron, Normah; Mat Jusoh, Hanapi; Darnis, Deny Susanti; Tan, Teng Ju (2018)
Anacardium occidentale Linn. (A. occidentale L.) or cashew tree is one of the popular tropical plant among various ethnics in Malaysia. Its leaves are commonly consumes as ulam in Southeast Asia. Its leaves possess an excellent source of bioactive compounds, which are associated with numerous health benefits including antidiabetic potency for the management of type 2 diabetes mellitus (T2DM). The management strategies for T2DM include to maintain the postprandial blood glucose level through the inhibition of α-amylase and to prevent the hydrolysis of glucagon like peptide-1 (GLP-1) through the inhibition of dipeptidyl peptidase IV (DPPIV). In this study, free, soluble ester and insoluble bound phenolic fractions from young and mature leaves of A. occidentale L. were extracted and analyzed for their phenolic compounds concentration using high performance liquid chromatography (HPLC). Subsequently, all fractions were investigated for their inhibitory effects on α-amylase and DPPIV enzymes activities. Both free (72.45 ± 3.6%) and soluble ester (83.40 ± 4.7%) phenolic fractions in the mature leaves extracts had significantly demonstrated greater α-amylase inhibitors than the young leaves. Likewise, soluble ester (4.09 ± 0.34 µg/ml) and insoluble bound (4.87 ± 0.32 µg/ml) phenolic fractions in the mature leaves extracts were significantly more effective in inhibiting DPPIV than the young leaves. As for fractions comparison, insoluble bound derived from the young leaves extract was more potent α-amylase inhibitor than free and soluble ester phenolic fractions (p<0.0001).Soluble ester and insoluble bound phenolic fractions showed stronger inhibitors of DPPIV than free phenolic (p<0.001), based on the maturity of the leaves. The interaction between fraction and maturity were significantly difference in both young and mature leaves of A. occidentale L. according to the α- amylase and DPPIV inhibition analyses (p<0.000). In conclusion, this study showed that A. occidentale L. extracts possessed antidiabetic properties which may potentially be used as an alternative treatment for the management of T2DM.